Phylogenetic and phenotypic analyses of streptomycetes isolated from local soil. - Tasrip, Nor Asmara; Mohd Desa, Mohd Nasir; Cheah, Yoke Kqueen; Chong, Pei Pei; Shamsudin, Mariana Nor (2012)
This study was to characterize the genetic and phenotypic features of soil isolates of Streptomyces. 39 isolates were harvested from various sites mainly around the University Agricultural Park, Universiti Putra Malaysia. Streptomyces griseus ATCC 10137 strain was also included for analysis as a reference strain (n = 40). Basic morphological characteristics and 16S rDNA-sequence homology confirmed the isolates as Streptomyces. The later was used to construct a phylogenetic tree which showed the diverse evolutionary pedigree of the isolates in 6 major clusters. Based on ISP-2 media, the observed aerial mass-color of the isolates were categorized as yellow (n = 15), grey (n = 9), brown (n = 7), white (n = 6) and others (n = 3). Antibacterial activities were assessed on MHA and TSA by perpendicular streak method against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Salmonella sp. and Enterococcus sp. MHA demonstrated 33 isolates with antibacterial activity against at least one of the test bacteria while that on TSA accounted for only 24. Chi-square analysis in 2x2 contingency tables identified a potential correlation between aerial mass of non-white color and antibacterial activities. This study supports Streptomyces as the diverse organism with potential rich source of natural antimicrobial compounds. Nevertheless, the observed association between the aerial mass-color and antibacterial property, as well as the effect of different test media on the antibacterial activities needs to be further investigated.